Pemetaan Infrastruktur Air Bersih Di Negeri Negeri Lima, Kabupaten Maluku Tengah - Rifyan Ruman; Willem Dominggus Nanlohy; Adnan Affan Akbar Botanri (EMPOWERMENT: Journal of Community Practice, 2026)
The availability of clean water is a fundamental necessity that plays a crucial role in supporting public health and welfare. However, the distribution of clean water infrastructure in Negeri Lima, Leihitu District, Central Maluku Regency, still faces various challenges that result in unequal access among communities. This community service activity aimed to map the clean water infrastructure spatially as a basis for planning and improving the effectiveness of the water distribution system. The methods employed included socialization and discussions with village authorities, participatory field surveys, coordinate data collection using GPS and mapping applications, and spatial data processing using a Geographic Information System (GIS) with ArcGIS software. The results revealed that the clean water infrastructure in Negeri Lima consists of springs, broncaptering facilities, reservoirs, distribution pipelines, drilled wells, and dug wells distributed across several hamlets. The resulting map successfully identified infrastructure locations, service coverage areas, and regions with limited access to clean water. In addition to producing digital and printed maps as the main outputs, the activity enhanced community participation and awareness regarding data-based water resource management. The generated clean water infrastructure map can serve as a valuable reference for decision-making, development planning, and the formulation of sustainable clean water service improvement programs in Negeri Lima